Amoris Laetitia Through the Lens of Disability. (2nd July 2016) - Cooreman-Guittin, Talitha
ABSTRACT: In April of 2016, Professor David Perry called the vision of Amoris Laetitia with regard to disability "a kind, charitable, paternalistic vision in which the function of the disabled is to demonstrate the goodness of those who care for them." This severe condemnation of the pontifical text appeals for a more detailed analysis.